National Dissemination of Multiple Evidence-Based Disease Prevention Programs: Reach to Vulnerable Older Adults - Towne, Samuel D.; Smith, Matthew Lee; Ahn, SangNam; Altpeter, Mary; Belza, Basia; Kulinski, Kristie Patton; Ory, Marcia G. (Frontiers in Public Health, 2015)
.